Environmental and Genetic Factors Associated with Solanesol Accumulation in Potato Leaves - Campbell, Raymond; Freitag, Sabine; Bryan, Glenn J.; Stewart, Derek; Taylor, Mark A. (Frontiers in Plant Science, 2016)
Solanesol is a high value 45-carbon, unsaturated, all-trans-nonaprenol isoprenoid. Recently solanesol has received particular attention because of its utility, both in its own right and as a precursor in the production of numerous compounds used in the treatment of disease states. Solanesol is found mainly in solanaceous crops such as potato, tomato, tobacco and pepper where it accumulates in the foliage. There is considerable potential to explore the extraction of solanesol from these sources as a valuable co-product. In this study we have characterised the genetic variation in leaf solanesol content in a biparental, segregating diploid potato population. We demonstrate that potato leaf solanesol content is genetically controlled and identify several quantitative trait loci associated with leaf solanesol content. Transient over-expression of genes from the methylerythritol 4-phosphate (MEP) and mevalonic acid (MVA) pathways, either singly or in combination, resulted in enhanced accumulation of solanesol in leaves of Nicotiana benthamiana, providing insights for genetically engineering the pathway. We also demonstrate that in potato, leaf solanesol content is enhanced by up to six-fold on exposure to moderately elevated temperature and show corresponding changes in expression patterns of MEP and MVA genes. Our combined approaches offer new insights into solanesol accumulation and strategies for developing a bio-refinery approach to potato production.